Pengembangan Aplikasi Web Tracer Study Fakultas Ilmu Komputer Universitas Brawijaya Menggunakan Metode Prototipe - Alfa Yolanda Putri Yulianti; Adam Hendra Brata; Herman Tolle (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Tracer study is a study to track the trace of graduates after two years since graduation with the aim of knowing the output of education in the form of transition from the world of higher education to the corporate world, the latest work situation, conformity and application of competence in the corporate world. At the Faculty of Computer Science, tracer study is carried out manually and data collection carried out using offline methods, which causes alumni outreach is not extensive and limited. This problem was felt by the student affairs department of the Faculty of Computer Science during the accreditation process in which the data from the tracer study was used as a complete assessment requirement. From these problems, the development of a web application tracer study is carried out to solve the perceived problem. Tracer study application is develop using the prototype method. The tracer study system was developed using PHP and web-based programming languages. Tracer study has 3 system sides, alumni side, company side and admin side. Unit testing is carried out using white box testing for 3 functions that produce average cyclomatic complexity value of 4, which means the system has a good level of complexity. Validation testing is done using black box testing for 37 test cases with 100% results, which means the system has meet all the functionality. Compatibility testing using Sortsite as a help tool with an outcome value of 100% compatible.